Virtual Tour Web System as a Guide and Entrepreneurial Tool for Tourism in Selayar - Mustika, Nur; Suhaeb, Sutarsi; Mirfan, Mirfan; Aman, Andryanto; Parewe, Andi Maulidinnawati Abdul Kadir; Lachlan, Nicholas (Aptisi Transactions On Technopreneurship (ATT), 2025)
This research aims to explore the use of virtual tour web systems as an innovation in developing the tourism sector in the Selayar Islands Regency, highlighting the potential of tourist destinations in the area. Using a Research and Development (R&D) method with an Interactive Multimedia System Design & Development (IMSDD) approach, this research produced an interactive system that allows users to explore tourist sites virtually. The system includes 360-degree panoramas, videos, maps, and tourist information. 34 respondents were involved in evaluating the system using the USE Questionnaire, focusing on three dimensions: Usability, Satisfaction, and Ease of Use. The results showed that the system was highly appreciated, with an average feasibility score of 81%, indicating that the Virtual Tour system is very feasible and suitable for promoting regional tourism as well as providing guidance for tourists to get to know more about tourist destinations virtually. These findings suggest that Virtual Tour technology can be an effective tool in enhancing tourism marketing, especially in post-pandemic times when physical travel is limited.